Masalah Kapasitas Kelembagaan dan Arah Kebijakan Kehutanan: Studi Tiga Kasus ((Problem of Institutional Capacity and Direction of Forestry Policy: Three Cases Study) - Hariadi Kartodihardjo (Jurnal Manajemen Hutan Tropika, 2006)
It has been shown by various references that performance of forestry development is determined by institutional capacity. This study was conducted to acquire knowledge of problem of forest management institution and policy change which should be able to be implemented. Studies in three locations and implementation of national policy indicated that forestry programs implemented by district/province government and central government were not accompanied by institutional strengthening efforts. The weaknesses of institution have been proven to be followed by policy failure to reach its target. Resistance to policy change stems from policy narrative and discource embedded in decision makers belief.Key words: institutional capacity, problem, policy narrative, discource